Electronic Media Marketing Mix to Increase Health Insurance Participation: Empirical Studi on BPJS Ketenagakerjaan Jayapura Branch (Jurnal Manajemen Bisnis, 2022)
This study was conducted to know the effect of each variable in the electronic media mix, consisting of television, radio, and internet media, significantly on increasing BPJS Ketenagakerjaan membership in the Jayapura Branch. This study uses questionnaire data and multiple linear regression analysis as research methods. The results of the study found that electronic media, consisting of television media, radio media, and internet media, had a significant influence on increasing BPJS Ketenagakerjaan membership in the Jayapura City Branch. Based on the results of simultaneous testing, the F-calculated value = 398,637 with a significance of 0.000 with an omission rate of 0.05, so it can be said that television media, radio media, and internet media together influence increasing BPJS Ketenagakerjaan membership in the Jayapura City Branch. So that the second hypothesis proposed can be accepted and proven true.